AZ-800 administering Windows Server hybrid core infrastructure - Abernathy, Robin M.; Bryan, Wes (Packt Publishing, 2024)
Explore the intricacies of Active Directory (AD) deployment for hybrid environments, beginning with an overview of the logical and physical components of AD Domain Services (AD DS). The course introduces key structural components and operational roles essential for deploying domain controllers both on-premises and in Azure, managing functional levels, and understanding Flexible Single Master Operations (FSMO) roles. As the course advances, it delves into more sophisticated configuration and management strategies. You'll learn about Read-Only Domain Controllers (RODCs), configuring sites and subnets, and using PowerShell to automate FSMO roles transfers. The course includes practical demonstrations on configuring trust relationships and managing replication across varied AD DS setups, arming you with vital skills for modern IT environments. In its concluding segments, the course focuses on integrating AD DS with Azure AD, creating a strong hybrid identity framework. Topics covered include implementing Azure AD Connect, managing synchronization services, and exploring Azure AD Connect Cloud Sync. Designed to build progressively, the course ensures a thorough understanding of deploying and managing AD in a hybrid setting and mastering the management of authentication and policies within your infrastructure.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Microsoft Windows server -- Study guides -- Examination; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet